2005
DOI: 10.1590/s0102-05362005000200006
|View full text |Cite
|
Sign up to set email alerts
|

Efeito da qualidade das sementes sobre a formação de mudas de alface

Abstract: O conhecimento preciso do potencial fisiológico das sementes permite, principalmente para espécies onde há transplante de mudas, a obtenção de mudas de tamanho e qualidade uniformes, com reflexos no desenvolvimento das plantas e, possivelmente, na produção final (SOU-ZA, 1977;MARCOS FILHO, 2001). Portanto, a produção de mudas e de plantas sadias depende em grande parte da utilização de sementes de boa qualidade.Sementes de alto potencial fisioló-gico são essenciais para que ocorra germinação rápida e uniforme … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
4
0
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 1 publication
3
4
0
3
Order By: Relevance
“…It was observed significant difference between the mean seedlings height with the irrigation systems utilized for all the lettuce cultivars, with means of 96 and 67 mm for the auto propelled lines and the fixed lateral lines irrigation systems, respectively (Table 2). These results agreed with those obtained by Franzin et al (2005) who found seedling heights between 79 and 104 mm. A probably reason why the lettuce seedlings irrigated with the autopropelled system presented a higher height than the those irrigated with the fixed system is because the fixed system operated with a fixed irrigation frequency, producing periods with elevated and low substrate water contents.…”
Section: Plant Behavior Evaluationsupporting
confidence: 93%
See 1 more Smart Citation
“…It was observed significant difference between the mean seedlings height with the irrigation systems utilized for all the lettuce cultivars, with means of 96 and 67 mm for the auto propelled lines and the fixed lateral lines irrigation systems, respectively (Table 2). These results agreed with those obtained by Franzin et al (2005) who found seedling heights between 79 and 104 mm. A probably reason why the lettuce seedlings irrigated with the autopropelled system presented a higher height than the those irrigated with the fixed system is because the fixed system operated with a fixed irrigation frequency, producing periods with elevated and low substrate water contents.…”
Section: Plant Behavior Evaluationsupporting
confidence: 93%
“…It is observed on , respectively, with the auto propelled system and 80 and 68 mg seedling -1 , respectively, with the fixed lines system. These results corroborate those found by Franzin et al (2005). The Monica cultivar aerial part dry phytomass was not affected by the irrigation system utilized.…”
Section: Plant Behavior Evaluationsupporting
confidence: 91%
“…Não houve diferença entre as doses de P 2 O 5 aos 0 e 15 meses de armazenamento das sementes, porém houve redução linear da germinação e vigor (IVG e primeira contagem) aos aos 25 meses quanto menor foi a dose de fósforo (Figura 1a, 1b e 1c Em estudos sobre métodos para a avaliação da qualidade de sementes de alface, Franzin et al (2005) concluíram que, dentre outros, a primeira contagem de germinação e a emergência em gerbox foram indicadas para a avaliação da qualidade das sementes. Pereira e Nascimento (2003) também concluíram que a primeira contagem de germinação foi um dos testes que detectou diferença entre lotes de sementes de alface quanto à qualidade.…”
Section: Resultsunclassified
“…Franzin et al (2005) concluded that seed lots with higher initial quality, as detected by laboratory germination and vigor tests, produced seedlings with greater weight. The same was observed by Rodo and Marcos Filho (2003) in onion.…”
Section: Resultsmentioning
confidence: 99%